The prevalence of attention-deficit hyperactivity disorder and its associated factors among children in Ethiopia, 2024: a systematic review and meta-analysis - Azmeraw, Molla; Temesgen, Dessie; Kassaw, Amare; Zemariam, Alemu Birara; Kerebeh, Gashaw; Abebe, Gebremeskel Kibret; Alamaw, Addis Wondmagegn; Abate, Biruk Beletew (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction: Attention-deficit hyperactivity disorder is one of the neuropsychiatric conditions that affect children. Its magnitude varies by area, ranging from 0.2% to 26.8%. Even though there is debates, culture and geographical location may have little or no influence on the epidemiology of ADHD world-wide. Despite this variation debates in prevalence and location, the national prevalence of ADHD is unknown in Ethiopia. Therefore, this study aimed to assess pooled prevalence of ADHD and its contributing factors among children.The electronic databases, including Google Scholar, PubMed, Scopus, EMBASE, Web of Science, ScienceDirect, and institutional repositories, were searched. The studies that covered prevalence and/or risk factors of ADHD in children were included in the collection. JBI quality rating tool was used to rate the quality of each study. The data was extracted using Microsoft Excel 2019, and the statistical analysis was performed using STATA 17.0. Using a random effect model, we evaluated the combined prevalence of ADHD and associated factors.The Cochrane Q-test and the I 2 test statistics were used to quantify the heterogeneity. Furthermore, publication bias was examined using the funnel plot graph and Egger's tests.Galbraith plot was employed to illustrate outliers. Sensitivity analysis was also applied.This study includes a total of six articles with 4,338 participants. The pooled prevalence estimates of ADHD was 8.81% (95%CI (4.52, 13.11);I 2 =96.95%; P=0.001). Age 6-12 AOR=3.51 ((95%CI: 1.38-5.64), I 2 = 0%; P = 0.001), being male AOR = 1.94 ((95%CI: 1.09-2.79), I 2 = 0%; P = 0.001), and living with single parents AOR = 4.92 ((95%CI: 1.24-861), I 2 = 0%; P = 0.001) were significant variables.One out of every twelve children in Ethiopia suffers from ADHD. Living with a single parent, being male, and being between the ages of 6 and 12 were risk factors for ADHD. A nationwide study with a sizable sample size may be required to ascertain the true impact of ADHD. It may be crucial to improve school health services in order to identify ADHD early and lessen its long-term effects.